Method for preparing crystal-form-controllable high-purity quartz from silicon wafer cutting waste
By acidic chemical purification and high-temperature oxidation treatment of silicon wafer cutting waste, high-purity amorphous quartz was prepared, and high-purity quartz with preset crystal forms was prepared through phase transformation reconstruction, which solved the problem of difficult removal of impurities in silicon wafer cutting waste and high-purity quartz preparation cost, and achieved efficient high-purity quartz recycling and high-value utilization.
Patent Information
- Application Number
- CN202510059884.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
Due to the fine particle size, strong surface activity and easy oxidation of silicon wafer cutting waste, it leads to the problem of difficult removal of impurities, high cost and low recovery during the preparation of high-purity quartz.
The waste is cut by drying and crushing, and the impurities are removed by acidic chemical purification. Then, it is fully contacted with the oxidation gas at high temperature to form high-purity amorphous quartz, and a preset crystalline high-purity quartz product is prepared through high-temperature phase transformation reconstruction.
The high-value utilization of silicon wafer cutting waste is achieved, the purity and recovery rate of high-purity quartz are improved, the production cost is reduced, and the problem of difficulty in removing impurities is solved.
Smart Images

Figure CN119822383A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing high-purity quartz with controllable crystal form from silicon slice cutting waste, belonging to the technical field of recycling and utilizing silicon slice cutting waste. Background Art
[0002] During the silicon wafer cutting process, a large amount of 6N grade high-purity silicon is lost to form silicon wafer cutting waste. With the rapid development of the photovoltaic industry, the amount of silicon wafer cutting waste has also increased significantly. Silicon wafer cutting waste has the characteristics of fine particle size, strong surface activity, and easy oxidation to form a surface oxide layer. At present, the main methods for recycling silicon wafer cutting waste include wet acid leaching, fire refining and combined processes. However, the presence of the surface oxide layer will hinder the contact between the acid and impurities during the wet acid leaching process, and will oxidize metal impurities during the fire refining process, increase the viscosity of the slag, hinder the separation of slag and silicon, and limit the purity and recovery rate of the recovered silicon. At present, in order to reduce the loss of high-purity silicon in the slicing process, reduce production costs, improve production efficiency and protect the environment, silicon wafer cutting is continuing to develop in the direction of "thinning" and "thinning". This results in the particle size of silicon wafer cutting waste becoming finer and finer. The finer the silicon wafer cutting waste, the stronger the surface activity, which further intensifies the oxidation phenomenon and produces a thicker surface oxide layer, making the purification of silicon more difficult. The difficulty of preparing high-purity silicon is greatly increased, the loss of silicon is aggravated, and the economic added value of recycled silicon is reduced.
[0003] High-purity quartz refers to quartz particles with a SiO2 content higher than 99.99%. Due to its unique physical and chemical properties, it plays an important role in the photovoltaic, semiconductor aviation, aerospace and electronics industries. At present, high-purity quartz is mainly prepared by purifying quartz minerals such as vein quartz, but it is extremely costly to increase the purity to above 4N8, making it difficult to apply industrially. Therefore, purifying and oxidizing the easily oxidized silicon wafer cutting waste to prepare high-purity quartz, increasing the economic added value of silicon wafer cutting waste, will help promote the industrial production of high-purity quartz materials. Summary of the invention
[0004] In view of the problems of silicon waste in existing silicon wafer cutting waste and the difficulty in removing impurities and high cost in the preparation process of high-purity quartz, the present invention proposes a method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste. In view of the characteristics of silicon wafer cutting waste that has a submicron particle size and is easy to oxidize, the silicon wafer cutting waste is dried and crushed, and impurities in the silicon wafer cutting waste are removed by acid leaching to obtain high-purity silicon powder; an oxidizing gas is introduced into the high-purity silicon powder so that the high-purity silicon powder and the oxidizing gas are fully contacted and oxidized at high temperature to obtain high-purity amorphous quartz; the high-purity amorphous quartz is reconstructed by high-temperature phase change to prepare a high-purity quartz product with a preset crystal form (α-quartz, cristobalite or tridymite), thereby realizing high-value utilization of silicon wafer cutting waste.
[0005] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0006] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles;
[0007] (2) subjecting the silicon wafer cutting waste particles to an acidic chemical purification treatment to deeply remove impurities to obtain high-purity silicon powder with a purity greater than 4N8;
[0008] (3) placing high-purity silicon powder in an oxidation reactor and heating it to a preset temperature, introducing an oxidizing gas so that the high-purity silicon powder and the oxidizing gas are fully contacted and oxidized at the preset temperature to obtain high-purity amorphous quartz;
[0009] (4) The high-purity amorphous quartz is subjected to high-temperature phase change reconstruction treatment to control the preparation of a high-purity quartz product with a preset crystal form, wherein the preset crystal form is α-quartz, cristobalite or tridymite.
[0010] Preferably, the particle size of the silicon wafer cutting waste particles in step (1) is less than 1 μm.
[0011] Preferably, the acid solution for the acidic chemical purification treatment in step (2) is one or more of sulfuric acid, hydrochloric acid, hydrofluoric acid, nitric acid, citric acid, and tartaric acid.
[0012] More preferably, the acid solution contains H + The concentration is 0.5-6 mol / L, the liquid-solid ratio of the acid solution to the silicon wafer cutting waste particles is 5-20:1 in mL:g, the leaching temperature is 40-300°C, and the stirring rate is 100-1000 rpm.
[0013] The oxidizing gas in step (3) is oxygen, air or water vapor or a mixture thereof.
[0014] Preferably, the thickness of the high-purity silicon powder in step (3) is 0.5-5 mm, the preset temperature is 300-800° C., and the introduction rate of the oxidizing gas is 50-500 m / s. 3 / h, oxidation time is 3 to 15h.
[0015] When the preset crystal form of the high-purity quartz product in step (4) is α-quartz, the temperature of the high-temperature phase change reconstruction treatment is 573 to 800° C., and the time is 1 to 20 hours;
[0016] When the preset crystal form of the high-purity quartz product is cristobalite, the temperature of the high-temperature phase change reconstruction treatment is 1350-1600°C and the time is 1-20h;
[0017] When the preset crystal form of the high-purity quartz product is cristobalite, the temperature of the high-temperature phase change reconstruction treatment is 870 to 1300°C, and the time is 1 to 20 hours.
[0018] The beneficial effects of the present invention are:
[0019] (1) The present invention performs an acidic chemical purification treatment on silicon wafer cutting waste particles for deep purification, lays high-purity silicon powder into an oxidation reactor and heats it to a preset temperature, introduces an oxidizing gas so that the high-purity silicon powder and the oxidizing gas are fully contacted and oxidized at a preset temperature to obtain high-purity amorphous quartz, and performs a high-temperature phase change reconstruction treatment on the high-purity amorphous quartz to controllably prepare a high-purity quartz product of a preset crystal form (α-quartz, cristobalite or tridymite), thereby realizing high-value utilization of silicon wafer cutting waste;
[0020] (2) The present invention uses silicon wafer cutting waste with high silicon content and easy oxidation as raw material, which has the advantage of strong raw material usability and has low requirements on parameters such as raw material form, particle size, and impurity content of silicon wafer cutting waste;
[0021] (3) The present invention can realize the directional preparation of quartz with a specific crystal form, has the advantages of easy adjustment and strong flexibility, and realizes the recycling and reuse of waste high-purity silicon resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0024] Example 1: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 56.57% and an initial block particle size of 5 to 10 cm;
[0025] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0026] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0027] (2) adding the silicon wafer cutting waste particles into hydrochloric acid with a concentration of 4 mol / L, and performing acidic chemical purification treatment at a temperature of 90° C. and a stirring rate of 600 r / min for 4 hours to deeply remove impurities, thereby obtaining high-purity silicon powder with a total impurity content of 15.26 ppmw; the liquid-to-solid ratio of the hydrochloric acid to the silicon wafer cutting waste particles is 5:1 in mL:g;
[0028] (3) High-purity silicon powder is spread into the oxidation reactor with a thickness of 2 mm and heated to a preset temperature (700 °C) at a rate of 300 m / s. 3 / h) of oxidizing gas (oxygen) to fully contact the high-purity silicon powder with the oxidizing gas (oxygen) at a preset temperature (700°C) for 5 hours to obtain high-purity amorphous quartz;
[0029] (4) High-purity amorphous quartz is placed at 700°C for a high-temperature phase change reconstruction treatment for 12 hours, and a high-purity quartz product with a preset crystal form (α-quartz) can be prepared;
[0030] The total impurity content of the high-purity quartz product of the crystal form (α-quartz) in this example is 15.26 ppmw.
[0031] Example 2: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 58.25% and an initial block particle size of 5 to 10 cm;
[0032] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0033] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0034] (2) adding the silicon wafer cutting waste particles into sulfuric acid with a concentration of 4 mol / L, and performing acidic chemical purification treatment at a temperature of 85° C. and a stirring rate of 650 r / min for 5 hours to deeply remove impurities, thereby obtaining high-purity silicon powder with a total impurity content of 19.54 ppmw; the liquid-to-solid ratio of the sulfuric acid to the silicon wafer cutting waste particles is 15:1 in mL:g;
[0035] (3) High-purity silicon powder is spread into the oxidation reactor with a thickness of 1 mm and heated to a preset temperature (750°C) at a rate of 100 m / s. 3 / h) of oxidizing gas (oxygen) to make high-purity silicon powder fully contact with oxidizing gas (oxygen) at a preset temperature (750°C) for 8h to obtain high-purity amorphous quartz;
[0036] (4) High-purity amorphous quartz is placed at a temperature of 650°C for a high-temperature phase change reconstruction treatment for 15 hours, and a high-purity quartz product with a preset crystal form (α-quartz) can be prepared;
[0037] The total impurity content of the high-purity quartz product of the crystal form (α-quartz) in this example is 19.54 ppmw.
[0038] Example 3: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 60.14% and an initial block particle size of 5 to 10 cm;
[0039] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0040] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0041] (2) adding the silicon wafer cutting waste particles into a mixed acid (the concentration of hydrofluoric acid in the mixed acid is 2 mol / L and the concentration of hydrochloric acid in the mixed acid is 4 mol / L), and performing an acidic chemical purification treatment at a temperature of 90° C. and a stirring rate of 700 r / min for 3 h to deeply remove impurities, thereby obtaining a high-purity silicon powder with a total impurity content of 7.16 ppmw; the liquid-to-solid ratio of the mixed acid to the silicon wafer cutting waste particles is 10:1 in mL:g;
[0042] (3) High-purity silicon powder was spread into the oxidation reactor with a thickness of 4.5 mm and heated to a preset temperature (800 °C) at a rate of 500 m / s. 3 / h) of oxidizing gas (air) to make high-purity silicon powder fully contact with oxidizing gas (air) at a preset temperature (800°C) for 12 hours to obtain high-purity amorphous quartz;
[0043] (4) High-purity amorphous quartz is placed at a temperature of 800°C for a high-temperature phase change reconstruction treatment for 10 hours, and a high-purity quartz product with a preset crystal form (α-quartz) can be prepared;
[0044] The total impurity content of the high-purity quartz product of the crystal form (α-quartz) in this example is 5.93 ppmw.
[0045] Example 4: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 57.41% and an initial block particle size of 5 to 10 cm;
[0046] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0047] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0048] (2) adding the silicon wafer cutting waste particles into a mixed acid (the tartaric acid concentration in the mixed acid is 2 mol / L and the hydrochloric acid concentration is 3 mol / L), and performing an acidic chemical purification treatment at a temperature of 80° C. and a stirring rate of 700 r / min for 2 h to deeply remove impurities, thereby obtaining a high-purity silicon powder with a total impurity content of 16.69 ppmw; the liquid-to-solid ratio of the mixed acid to the silicon wafer cutting waste particles is 10:1 in mL:g;
[0049] (3) High-purity silicon powder is spread into the oxidation reactor with a thickness of 0.5 mm and heated to a preset temperature of 800 °C. The feed rate is 50 m / s. 3 / h) of oxidizing gas (air) to make high-purity silicon powder fully contact with oxidizing gas (air) at temperature (800°C) for 8h to obtain high-purity amorphous quartz;
[0050] (4) High-purity amorphous quartz is placed at a temperature (1500°C) for a high-temperature phase change reconstruction treatment for 14 hours, and high-purity cristobalite of a preset crystal form (cristobalite) can be prepared in a controlled manner;
[0051] The total impurity content of the high-purity quartz product of the crystal form (cristobalite) in this embodiment is 16.69 ppmw.
[0052] Example 5: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 58.91% and an initial block particle size of 5 to 10 cm;
[0053] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0054] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0055] (2) adding the silicon wafer cutting waste particles into sulfuric acid with a concentration of 5 mol / L, and performing acidic chemical purification treatment at a temperature of 90° C. and a stirring rate of 800 r / min for 2.5 hours to deeply remove impurities, thereby obtaining high-purity silicon powder with a total impurity content of 18.96 ppmw; the liquid-to-solid ratio of the sulfuric acid to the silicon wafer cutting waste particles is 8:1 in mL:g;
[0056] (3) High-purity silicon powder was spread into the oxidation reactor with a thickness of 3 mm and heated to a preset temperature (740 °C) at a rate of 350 m / s. 3 / h) of oxidizing gas (oxygen) to make high-purity silicon powder and oxidizing gas (oxygen) fully contact and oxidize at a preset temperature (740°C) for 5 hours to obtain high-purity amorphous quartz;
[0057] (5) High-purity amorphous quartz is placed at a temperature of 1590°C for a high-temperature phase change reconstruction treatment for 11 hours, and a high-purity quartz product with a preset crystal form (cristobalite) can be prepared;
[0058] The total impurity content of the high-purity quartz product of the crystal form (cristobalite) in this example is 18.96 ppmw.
[0059] Example 6: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 55.84% and an initial block particle size of 5 to 10 cm;
[0060] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0061] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0062] (2) adding the silicon wafer cutting waste particles into hydrochloric acid with a concentration of 5 mol / L, and performing acidic chemical purification treatment at a temperature of 200° C. and a stirring rate of 700 r / min for 2.5 hours to deeply remove impurities, thereby obtaining high-purity silicon powder with a total impurity content of 9.73 ppmw; the liquid-to-solid ratio of the hydrochloric acid to the silicon wafer cutting waste particles is 12:1 in mL:g;
[0063] (3) High-purity silicon powder is spread into the oxidation reactor with a thickness of 1 mm and heated to a temperature of 620°C. The feed rate is 400 m / s. 3 / h) of oxidizing gas (air) to make high-purity silicon powder and oxidizing gas (air) fully contact and oxidize at temperature (620°C) for 7h to obtain high-purity amorphous quartz;
[0064] (4) High-purity amorphous quartz is placed at a temperature (1360°C) for a high-temperature phase change reconstruction treatment for 20 hours, and a high-purity quartz product with a preset crystal form (cristobalite) can be prepared;
[0065] The total impurity content of the high-purity quartz product of the crystal form (cristobalite) in this embodiment is 9.73 ppmw.
[0066] Example 7: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 58.15% and an initial block particle size of 5 to 10 cm;
[0067] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0068] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0069] (2) adding the silicon wafer cutting waste particles into 6 mol / L hydrochloric acid, and performing acidic chemical purification treatment at a temperature of 90° C. and a stirring rate of 800 r / min for 2 h to deeply remove impurities, thereby obtaining high-purity silicon powder with a total impurity content of 11.87 ppmw; the liquid-to-solid ratio of the hydrochloric acid to the silicon wafer cutting waste particles is 10:1 in mL:g;
[0070] (3) High-purity silicon powder was spread into the oxidation reactor with a thickness of 3 mm and heated to a temperature of 680°C. The feed rate was 250 m / s. 3 / h) of oxidizing gas (oxygen) to make high-purity silicon powder and oxidizing gas (oxygen) fully contact and oxidize at temperature (680°C) for 6h to obtain high-purity amorphous quartz;
[0071] (4) High-purity amorphous quartz is placed at a temperature (1000°C) for a high-temperature phase change reconstruction treatment for 12 hours, and a high-purity quartz product with a preset crystal form (tridymite) can be prepared;
[0072] The total impurity content of the high-purity quartz product of the crystal form (tridymite) in this example is 11.87 ppmw.
[0073] Example 8: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 52.73% and an initial block particle size of 5 to 10 cm;
[0074] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0075] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0076] (2) adding the silicon wafer cutting waste particles into a mixed acid (the hydrochloric acid concentration in the mixed acid is 2 mol / L and the sulfuric acid concentration is 3 mol / L), and performing an acidic chemical purification treatment at a temperature of 85° C. and a stirring rate of 700 r / min for 3 hours to deeply remove impurities, thereby obtaining a high-purity silicon powder with a total impurity content of 14.37 ppmw; the liquid-to-solid ratio of the mixed acid to the silicon wafer cutting waste particles is 8:1 in mL:g;
[0077] (3) High-purity silicon powder was spread into the oxidation reactor with a thickness of 2 mm and heated to a temperature of 730°C. The feed rate was 400 m / s. 3 / h) of oxidizing gas (steam) to make high-purity silicon powder and oxidizing gas (steam) fully contact and oxidize at a preset temperature (730°C) for 7 hours to obtain high-purity amorphous quartz;
[0078] (4) High-purity amorphous quartz is placed at a temperature (1290°C) for a high-temperature phase change reconstruction treatment for 10 hours, and a high-purity quartz product with a preset crystal form (tridymite) can be prepared;
[0079] The total impurity content of the high-purity quartz product of the crystal form (tridymite) in this example is 14.37 ppmw.
[0080] Example 9: The silicon wafer cutting waste in this example is a filter cake obtained by plate and frame filtration of silicon wafer cutting slurry, with an initial water content of 59.55% and an initial block particle size of 5 to 10 cm;
[0081] A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, the specific steps are as follows:
[0082] (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles with a particle size of less than 1 μm;
[0083] (2) adding the silicon wafer cutting waste particles into a mixed acid (the sulfuric acid concentration in the mixed acid is 4 mol / L and the citric acid concentration is 2 mol / L), and performing an acidic chemical purification treatment at a temperature of 85° C. and a stirring rate of 800 r / min for 5 hours to deeply remove impurities, thereby obtaining a high-purity silicon powder with a total impurity content of 12.57 ppmw; the liquid-to-solid ratio of the mixed acid to the silicon wafer cutting waste particles is 10:1 in mL:g;
[0084] (3) High-purity silicon powder was spread into the oxidation reactor with a thickness of 1.5 mm and heated to a temperature of 780°C. The feed rate was 200 m / s. 3 / h) of oxidizing gas (water vapor) to make high-purity silicon powder and oxidizing gas (water vapor) fully contact and oxidize at a preset temperature (780°C) for 8 hours to obtain high-purity amorphous quartz;
[0085] (4) High-purity amorphous quartz is placed at a temperature (880°C) for a high-temperature phase change reconstruction treatment for 15 hours, and a high-purity quartz product with a preset crystal form (tridymite) can be prepared;
[0086] The total impurity content of the high-purity quartz product of the crystal form (tridymite) in this example is 12.57 ppmw;
[0087] The impurity content results of the high purity quartz products in Examples 1 to 9 are shown in Table 1 below;
[0088] Table 1 Impurity content results of high purity quartz products in the examples (ppmw)
[0089]
[0090] As can be seen from Table 1, the high-purity quartz products of the preset crystal form (α-quartz, cristobalite or tridymite) in Examples 1 to 9 have low contents of impurities Fe, Al and Ni, which can achieve high-value utilization of silicon wafer cutting waste.
[0091] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste, characterized in that: The specific steps are as follows: (1) drying and dehydrating the silicon wafer cutting waste block material, and crushing it to obtain silicon wafer cutting waste particles; (2) subjecting the silicon wafer cutting waste particles to an acidic chemical purification treatment to deeply remove impurities to obtain high-purity silicon powder with a purity greater than 4N8; (3) placing high-purity silicon powder in an oxidation reactor and heating it to a preset temperature, introducing an oxidizing gas so that the high-purity silicon powder and the oxidizing gas are fully contacted and oxidized at the preset temperature to obtain high-purity amorphous quartz; (4) The high-purity amorphous quartz is subjected to high-temperature phase change reconstruction treatment to control the preparation of a high-purity quartz product with a preset crystal form, wherein the preset crystal form is α-quartz, cristobalite or tridymite.
2. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: The particle size of the silicon wafer cutting waste particles in step (1) is less than 1 μm.
3. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: The acid solution for the acidic chemical purification treatment in step (2) is one or more of sulfuric acid, hydrochloric acid, hydrofluoric acid, nitric acid, citric acid, and tartaric acid.
4. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: The acid solution contains H + The concentration is 0.5-6 mol / L, the liquid-solid ratio of the acid solution to the silicon wafer cutting waste particles is 5-20:1 in mL:g, the leaching temperature is 40-300°C, and the stirring rate is 100-1000 rpm.
5. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: The oxidizing gas in step (3) is one or more of oxygen, air and water vapor.
6. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: Step (3) The thickness of the high-purity silicon powder is 0.5-5 mm, the preset temperature is 300-800° C., and the introduction rate of the oxidizing gas is 50-500 m / s. 3 / h, oxidation time is 3 to 15h.
7. The method for preparing high-purity quartz with controllable crystal form from silicon wafer cutting waste according to claim 1, characterized in that: Step (4) When the preset crystal form of the high-purity quartz product is α-quartz, the temperature of the high-temperature phase change reconstruction treatment is 573 to 800° C., and the time is 1 to 20 hours; When the preset crystal form of the high-purity quartz product is cristobalite, the temperature of the high-temperature phase change reconstruction treatment is 1350-1600°C and the time is 1-20h; When the preset crystal form of the high-purity quartz product is cristobalite, the temperature of the high-temperature phase change reconstruction treatment is 870 to 1300°C, and the time is 1 to 20 hours.